1994
DOI: 10.1080/03014469400003562
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of heritability of immunoglobulin levels

Abstract: Heritability of IgA, IgG and IgM levels was studied in 85 MZ and DZ twin pairs of both sexes. Immunoglobulin concentrations were determined by single radial diffusion. Significantly higher geometric mean of IgM level in females than males was demonstrated. Heritability coefficients h2, F and VG/VE were higher in male than female twins. This suggests that genetic factors play a more important role in males as compared with females in regulating the three immunoglobulin levels. Quantitative comparison of genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…Cryptococcosis was more common among men in the pre-AIDS era than among women (13) and in several cohorts of HIV-infected individuals in the United States and France than among Ugandans (26,29,34). Interestingly, higher levels of immunoglobulin have been reported among females than among males (38,55). Women comprised 67% of the cohort in our study, but there were no differences in antibody levels based on gender in our adjusted analyses.…”
Section: Deficiency Of Cd27contrasting
confidence: 36%
“…Cryptococcosis was more common among men in the pre-AIDS era than among women (13) and in several cohorts of HIV-infected individuals in the United States and France than among Ugandans (26,29,34). Interestingly, higher levels of immunoglobulin have been reported among females than among males (38,55). Women comprised 67% of the cohort in our study, but there were no differences in antibody levels based on gender in our adjusted analyses.…”
Section: Deficiency Of Cd27contrasting
confidence: 36%
“…In this field, enormous studies have been conducted. [6,7] Results for IgA and IgG levels are similar in both sexes, but for IgM levels, it has been observed that, in females, the IgM level is higher than in male subjects, [23,26] and some studies found a relationship between number of X chromosomes and IgM concentration. [8,21,22] In most sciences, such as immunology, an approved, authoritative, global standard reference interval has been prepared which is profitable in laboratory and clinical tests.…”
Section: Discussionmentioning
confidence: 99%
“…This parallels the observed male predominance in the literature. However, also among healthy controls low IgM levels are more common in males [18][19][20][21], and there are some reports of low serum IgM levels among fathers of patients [22,23]. It would be of interest to investigate this gender difference further.…”
Section: Selective Igm Deficiencymentioning
confidence: 99%